Exploring the occurences of stress, anxiety, and depression among 4th year college student (A.Y.2018-2019) from State University and Colleges (SUC's) in Tacloban City using the depression, anxiety, and stress scale-21 (DASS21). - Pedere, Paul Vincent C.; Resquicio, Joshua C. (Tacloban City Paul Vincent C. Pedere and Joshua C. Resquicio, 2019)
This study evaluated the factors associated with stress, anxiety, and depression on selected 4 year college students (n = 448) in State Universitys and Colleges (SUC's) located in Tacloban City. The researchers utilized the DASS-21 in analyzing the level of stress, anxiety, and depression of the selected participants. Results suggested that; school had a significant effect on an individual's level of stress (p = .000). On the other hand, variables such as Gender (stress p =.636; anxiety p = .557; depression p =.104), Religion (stress p =.322; anxiety p =.266; depression p =.208), Residence (stress p =.414; anxiety p =.727; depression p =.141), Parent's Marital Status (stress p =.458; anxiety p =.671; depression p =.372), Parents' Socio-economic Status (stress p =.840; anxiety p =.575; depression p =.845), Alcohol (stress p =.054; anxiety p =.790; depression p =.116), and Smoking (stress p =.058; anxiety p =.675; depression p =.079) had no significant effect with respect to the person's mental health. Based on the results, on the stress category; 48.32% of the sample belong to mild, 15.40% belong to moderate, 4.91% belong to severe, and 1.56% belong to extremely severe. For Anxiety category; 6.25% belong to mild, 31.70% belong to moderate, 17.63% belong to severe, and 26.12% belong to extremely severe. And for Depression category; 18.53% belong to mild, 30.80% belong to moderate, 8.26% belong to severe, and 8.26% also belong to extremely severe. The findings made the researchers conclude that; on the stress category, most of students felt either anormal or mild level of stress. In contrast, on the anxiety category, most of students had a moderate to extremely severe level of anxiety. And for the depression variable, most of the students fell on either normal or moderate level of anxiety.
Undergraduate Research (B.A.Psychology) -- University of the Philippines, Tacloban.